2022
DOI: 10.7717/peerj.13087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precipitation change on the photosynthetic performance of Phragmites australis under elevated temperature conditions

Abstract: Background As a fundamental metabolism, leaf photosynthesis not only provides necessary energy for plant survival and growth but also plays an important role in global carbon fixation. However, photosynthesis is highly susceptible to environmental stresses and can be significantly influenced by future climate change. Methods In this study, we examined the photosynthetic responses of Phragmites australis (P. australis) to three precipitation treatments (control, decreased 30%, and increased 30%) under two the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…The leaf chlorophyll content is an important indicator of direct foliage damage and is strongly related to plant productivity (Du 2017). As a fundamental metabolism, leaf photosynthesis not only provides the necessary energy for plant survival and growth but also plays an important role in carbon fixation (Teng 2022). Certain species of Smilax are often found on the edge areas of forest openings (Sofiah 2019), for example Smilax gigantea Merr.…”
Section: Discussionmentioning
confidence: 99%
“…The leaf chlorophyll content is an important indicator of direct foliage damage and is strongly related to plant productivity (Du 2017). As a fundamental metabolism, leaf photosynthesis not only provides the necessary energy for plant survival and growth but also plays an important role in carbon fixation (Teng 2022). Certain species of Smilax are often found on the edge areas of forest openings (Sofiah 2019), for example Smilax gigantea Merr.…”
Section: Discussionmentioning
confidence: 99%
“…The results of correlation analysis in this study showed that the average annual temperature (Bio1) and average annual precipitation (Bio12) were signi cantly negatively correlated with berberine alkaloid content, while they were signi cantly or highly signi cantly positively correlated with columbin content, i.e., an increase in temperature within a certain range may be more favorable to the accumulation of columbin 46 , and a decrease in temperature may be more favorable to the accumulation of alkaloids; the standard deviation of the seasonal variation (Bio4) was signi cantly positively correlated with berberine alkaloid content, while it was signi cantly negatively correlated with columbin content, suggesting that greater seasonal temperature variation favors the increase of alkaloids 47,48 . Precipitation plays an important regulatory role in the growth cycle of plants, regulating and in uencing growth, development, and other physiological activities 49,50 , for example, Rahmati et al showed that severe water de cit led to a decrease in the dry matter mass of peach fruits, leafy stems, and shoots, but led to an increase in the content of soluble sugars in the fruits 51 , suggesting that the amount of water availability is important for the distribution of the plant, its growth, development and the accumulation of secondary metabolites has a decisive in uence. In this study, water saturated vapor pressure (Vapr) was signi cantly and positively correlated with berberine alkaloid content, and warmest season precipitation (Bio18) was highly and signi cantly positively correlated with columbin at the 0.001 level, suggesting that more precipitation may be more favorable for columbin and alkaloid accumulation.…”
Section: Suitable Areas and Ecological Characterization Of Tinospora ...mentioning
confidence: 99%
“…Drought and heat stress can impede photosynthesis by interfering with light energy capture, the PSII, the xanthophyll cycle and associated enzyme activity (Stasik and Jones 2007). On these grounds, photosynthesis has been used to detect and quantify damage in response to drought and heat stress in several crops, including wheat (Sharma et al 2015), legumes (Teng et al 2022), and maize (Li et al 2018). Photosynthesis is generally the result of a combination of stomatal and non-stomatal regulation mechanisms.…”
mentioning
confidence: 99%